Transcriptomic Analysis Reveals the Protection of Astragaloside IV against Diabetic Nephropathy by Modulating Inflammation. (14th August 2020) - Zhang, Yudi; Tao, Chunhe; Xuan, Chen; Jiang, Junyan; Cao, Wenfu
Abstract : Background . Diabetic nephropathy (DN) is one of the leading causes of end-stage kidney disease. Recently, there is no specific drug available to block the kidney damage. Astragaloside IV (AS-IV) is a major active component of Astragalus membranaceus (Fisch) Bge and has been demonstrated to benefit the kidney functions. This study explores the potential pharmacological action of AS-IV in DN of rats. Methods . Male Sprague-Dawley rats were fed with high-fat diet and injected with streptozotocin to induce diabetes. The diabetic rats were randomized and treated with vehicle or AS-IV (80 mg/kg) daily by gavage for 12 weeks as the DN or AS-IV group, respectively. The normal control rats were fed with normal chow and injected with vehicles (n = 8 per group). These rats were monitored for diabetes- and kidney function-related measures. The expression profiles of gene mRNA transcripts in the kidney tissues were analyzed by RNA-seq and quantitative RT-PCR. The levels of advanced glycation end products (AGEs), IL-1 β, and IL-18 in the serum samples and kidney tissues were quantified by ELISA. The levels of collagen IV (COL-4) and fibronectin (FN) expression in kidney tissues were examined by immunohistochemistry and Western blot. Results . In comparison with the DN group, AS-IV treatment significantly reduced blood glucose levels, food and water consumption, 24 h urine, renal index values, 24 h urine total proteins, blood urea nitrogen (BUN) levels, and creatinine clearance rates (CCR), accompanied by minimizing the DN-induced early kidney damages, fibrosis, and microstructural changes. Furthermore, AS-IV treatment significantly modulated the DN-altered gene transcription profiles in the kidney of rats, particularly for inflammation-related genes, including the nucleotide-binding oligomerization domain-like receptor signaling, which was validated by quantitative RT-PCR. AS-IV treatment significantly decreased the levels of serum and kidney AGEs, IL-1 β, and IL-18 expression and fibrosis indexes in the kidney of rats. Conclusion . AS-IV treatment ameliorated the severity of DN by inhibiting inflammation-related gene expression in the kidney of rats.